The Impact of Recovery Practices Adopted by Professional Tennis Players on Fatigue Markers According to Training Type Clusters - Poignard, Mathilde; Guilhem, Gaël; de Larochelambert, Quentin; Montalvan, Bernard; Bieuzen, François (Frontiers in Sports and Active Living, 2020)
Introduction: Modern tennis players face congested schedules that force the adoption of various recovery strategies. Thus, recovery must be fine-tuned with an accurate quantification of its impacts, especially with regards to training-induced fatigue. The present study aimed to examine the training type clusters and recovery practices adopted by elite tennis players under ecological training conditions. The respective impacts of training type clusters and recovery techniques on subjective variables, which reflect the players' recovery perceptions, were subsequently determined. Methods: During 15 consecutive months, a total of 35 elite tennis players filled out questionnaires to report their daily training load, training session content, adopted recovery modalities after training, and perceived recovery. Results: The hierarchical analysis identified three clusters: “combined tennis and S&C training”, “predominant tennis training” and “predominant S&C training”. Muscle soreness and perceived fatigue were not significantly different among these three clusters (p=0.07 to 0.65). Across the 146 recorded training and recovery sessions, players primarily employed a combination of 2 or 3 modalities, with cooling strategies being the most widely used technique (87.6%). Mixed linear models revealed that independent of training clusters, cooling strategies significantly reduced muscle soreness (Δmuscle soreness: β=-1.00, p=0.02). Among the cooling techniques used, whole-body cryotherapy induced a greater perceived recovery than cold-water immersion (p=0.02). Conclusion: These results showed that perceived recovery was not sensitive to training clusters or the associated acute training load. However, cooling strategies were relevant for the alleviation of tennis training-induced soreness. This study represents an initial step towards a periodized approach of recovery interventions, based on the interactions between training load, training contents, and perceived recovery.